The Impact of Cognitive and Affective Trust on Customer Loyalty in Indonesian M-Commerce Platforms - Subhan, Zhafira Nur (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
Mobile payment (m-payment) systems have played a major role in the explosive expansion of mobile commerce (m-commerce) in Indonesia. The purpose of this study is to look into how consumer loyalty in m-commerce platforms is shaped by cognitive and affective trust. The study investigates how consumer loyalty to m-commerce platforms is impacted by the cognitive and emotive aspects of trust, which are influenced by perceptions of security, trust in m-payment systems and business reputation. 314 active users of m-commerce sites including Shopee, Tokopedia, and Bukalapak in the JABODETABEK region were given surveys as part of the quantitative research. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to examine the data. The findings demonstrate that security perceptions have a beneficial impact on m-payment system cognitive and emotional trust, which in turn raises m-commerce trust. Furthermore, customer trust in m-commerce platforms is significantly impacted by a company's reputation. The report emphasizes how crucial it is to protect security and cultivate a solid company reputation to encourage customer loyalty. These results imply that m-commerce companies in Indonesia should give equal weight to the emotional and rational aspects of trust to increase consumer loyalty, especially by enhancing perceived security and building a solid reputation for their business.